Health program for prEvention of cardiovascuLar disEases based on a risk screeNing strategy with Ankle-brachial index: HELENA study protocol - Domínguez-Armengol, Gina; Ribas-Aulinas, Francesc; Balló, Elisabet; Alzamora-Sas, Maite; Serrat-Costa, Mar; Ruiz-Comellas, Anna; Forcadell-Peris, Maria Jose; Toran, Pere; Martí-Lluch, Ruth; Ponjoan, Anna; Blanch, Jordi; Alves-Cabratosa, Lia; et al. (Frontiers in Public Health, 2025)
IntroductionThe use of risk functions to individualize preventive interventions is a key strategy in the primary prevention of coronary heart diseases (CHD). Unfortunately, most risk functions still fail to identify many individuals who will experience a cardiovascular (CV) event. Detecting individuals with asymptomatic peripheral artery disease (PAD) with a new risk function could improve CV risk classification. The aim is to evaluate the effectiveness of integrating an ankle-brachial index (ABI) program into the current CHD risk detection strategy to identify populations at high risk of asymptomatic PAD, reducing the incidence of CHD and mortality in those aged 50 to 74 years.MethodsThis study is a pragmatic randomized cluster trial. A total of 274 primary care centers will be randomized into two groups that will either maintain the current CHD risk detection strategy or add a screening program to detect asymptomatic PAD using ABI. In routine clinical practice, 10-year CHD and PAD risk are assessed using the Framingham-adapted (REGICOR) function and the REASON function, respectively. The study population will consist of patients aged 50 to 74 years with a CHD risk ≥ 7% and PAD risk ≥ 7%, making them candidates for an ABI measurement. Cases with an ABI result ≤ 0.9 will have their CHD reclassified as high or very high by doubling the initial REGICOR score and receive the recommendations of the lipid and cardiovascular risk guideline. The primary outcomes will be hard CHD, major adverse cardiovascular events (MACE), all-cause mortality, and improvement in CVD risk factors. Secondary outcomes include CHD (a composite of angina and hard CHD), cerebrovascular disease, and adverse effects from lipid-lowering medication. Survival analysis will estimate the effectiveness of adding the ABI screening strategy, with Cox models (intention-to-treat) and marginal structural models controlling for confounding variables.Results and discussionDirect health improvements in the intervened population are expected, including a reduction in CHD incidence and its risk factors. This project is particularly valuable, as delays in screenings and control of CV risk factors have accumulated after the COVID-19 pandemic. Therefore, this work is expected to help recover and enhance cardiovascular risk prevention efforts.Clinical trial registrationClinicalTrials.gov, NCT05884840.